2021
DOI: 10.1021/acs.organomet.1c00336
|View full text |Cite
|
Sign up to set email alerts
|

Terminal Mo Carbide and Carbyne Reactivity: H2 Cleavage, B–C Bond Activation, and C–C Coupling

Abstract: Transition-metal carbides have been posited as intermediates in the upgrading of C 1 feedstocks, including the Fischer− Tropsch synthesis of higher olefins from CO and H 2 . Still, molecular examples remain rare, and their reactivity is poorly understood. In a molecular platform supported by a flexible terphenyl diphosphine ligand, the important C−C coupling step was previously demonstrated on the reaction of Mo carbide and carbene species with CO. Methylidyne and methylidene complexes were accessible on seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…Biaryl phosphine ligands (Buchwald‐type ligands) are widely used in palladium and gold chemistry, due to stabilizing effect of the metal‐arene π‐interaction. Similar ligands with two phosphorous atoms have also attracted some attention because such chelating systems allow for a variable metal‐arene coordination while maintaining the stability of the complex through the strong M−P bonds [1–4] . To the best of our knowledge, almost all of these ligands have been synthesized by reactions of the corresponding lithium or magnesium aromatic derivatives with R 2 PCl.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Biaryl phosphine ligands (Buchwald‐type ligands) are widely used in palladium and gold chemistry, due to stabilizing effect of the metal‐arene π‐interaction. Similar ligands with two phosphorous atoms have also attracted some attention because such chelating systems allow for a variable metal‐arene coordination while maintaining the stability of the complex through the strong M−P bonds [1–4] . To the best of our knowledge, almost all of these ligands have been synthesized by reactions of the corresponding lithium or magnesium aromatic derivatives with R 2 PCl.…”
Section: Methodsmentioning
confidence: 99%
“…The dissolution in CDCl 3 results in slow decomposition of 1 and therefore the spectra were recorded in CD 2 Cl 2 solution. 1 H NMR (400 MHz, CD 2 Cl 2 ): δ = 7.65 (dd, J = 7.6, 3.6 Hz, 1H), 7.52-7.22 (m, 17H), 6.92 (dd, J = 7.7, 3.7 Hz, 1H). 31 P NMR (162 MHz, CD 2 Cl 2 ): δ = À 8.88.…”
Section: Synthesis Of Diphenylphosphino-tolanementioning
confidence: 99%
See 2 more Smart Citations
“…the protonation-hydride uptake sequence in Figure ). However, this reaction suffers from low selectivity and release of the diphosphine ligand. In searching for a Lewis-acid that would render the reaction selective toward protonation of the terminal carbide ligand, it was found that [(2,2′′- i Pr 2 P-terph)­(OC)­MoC] reacts with BPh 3 to generate a spectroscopically observable carbide-borane adduct, [(2,2′′- i Pr 2 P-terph)­(OC)­MoC–BPh 3 ].…”
Section: Addendum: Additions Made During Manuscript Revisionmentioning
confidence: 99%